Market-based governance : supply side, demand side, upside, and downside - Donahue, John D.; Nye, Joseph S. (Brookings Institution Press, 2002)
Annotation The latest in a series exploring twenty-first-century governance, this new volume examines the use of market means to pursue public goals.